2019
DOI: 10.3390/s19112438
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Instrumented Insoles for Step Counting, Posture and Activity Recognition: A Systematic Review

Abstract: With the growing interest in daily activity monitoring, several insole designs have been developed to identify postures, detect activities, and count steps. However, the validity of these devices is not clearly established. The aim of this systematic review was to synthesize the available information on the criterion validity of instrumented insoles in detecting postures activities and steps. The literature search through six databases led to 33 articles that met inclusion criteria. These studies evaluated 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 62 publications
(229 reference statements)
2
31
0
Order By: Relevance
“…These insoles can extract gait features and help in classification of PD stages and in daily monitoring for rehabilitation purposes. The results of the comparative study [34] emphasize that the data validity of smart insoles is 75% to 100% accurate, 75% to 100% precise, and the specificity lies between 73% to 100%. In this way, we can say that smart wearables [40] allow quantitative, objective, and reliable evaluation of motor activities.…”
Section: Insoles Models and Technical Featuresmentioning
confidence: 89%
See 1 more Smart Citation
“…These insoles can extract gait features and help in classification of PD stages and in daily monitoring for rehabilitation purposes. The results of the comparative study [34] emphasize that the data validity of smart insoles is 75% to 100% accurate, 75% to 100% precise, and the specificity lies between 73% to 100%. In this way, we can say that smart wearables [40] allow quantitative, objective, and reliable evaluation of motor activities.…”
Section: Insoles Models and Technical Featuresmentioning
confidence: 89%
“…Not all the aforementioned devices in [27][28][29][30][31][32][33] are appropriate for daily routines in people with Parkinson's disorder, and it is hard to find a single wearable device for diagnosis, monitoring, and rehabilitation of PD. A systematic review in [34] provided a potential solution for continuous and unobstructed appraisal of Parkinson's patients that resides in smart insoles.…”
Section: Insoles Models and Technical Featuresmentioning
confidence: 99%
“…Banknote identifier [84] Difficult to use, complex user input Prosthetic Damping Control [85] Manual control required, low comfortability, high complexity Toto Intelligence Toilet II [86] Over-complexity, difficult to use Head driven mouse for smartwatch [87] Low practicality, high learning curve Smart armchair [88] Low usefulness, complex to adjust and control Home Automation Kit for smart home control [89] High complexity, difficult to use Smart insoles [90] Low reliability Garmin Vivofit activity tracker [91] Low usability, high learning curve…”
Section: Examples Of Failurementioning
confidence: 99%
“…toe protection and slip resistance, a sensor built into these shoes would be a practical and relatively easily implementable solution in an occupational setting. Previous work has shown that an accelerometer placed on a shoe has similar accuracy in predicting activities as other placements [ 6 ], but the performance of shoe based sensors have not been evaluated in a free-living setting previously [ 7 ].…”
Section: Introductionmentioning
confidence: 99%